Front right: Elise Botha, wife of South African president P.W. Botha. Front left: Mrs. Tshabalala, mayor of Soweto, Johannesburg - Weinberg, Paul,
Front right: Elise Botha, wife of South African president P.W. Botha. Front left: Mrs. Tshabalala, mayor of Soweto, Johannesburg.